1997
DOI: 10.1046/j.1365-2559.1997.3310898.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular lymphomatosis: a clinicopathological study of two cases presenting as an interstitial lung disease

Abstract: These cases and 10 previous reports illustrate the need to include intravascular lymphomatosis in the differential diagnosis of interstitial lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 37 publications
6
37
0
Order By: Relevance
“…In fact, some patients presenting with pulmonary symptoms were initially treated under the impression of pneumonia or interstitial lung disease. Likewise, previous case reports describe the interstitial lung disease-like pulmonary presentation of IVLBCL [18,19,20,21,22]. As shown by patients in this study, IVLBCL should be considered in the differential diagnosis of unexplained pulmonary presentations such as unexplained hypoxemia, interstitial lung disease or ground-glass opacity accompanied by systemic symptoms or signs of multi-organ involvement.…”
Section: Discussionsupporting
confidence: 77%
“…In fact, some patients presenting with pulmonary symptoms were initially treated under the impression of pneumonia or interstitial lung disease. Likewise, previous case reports describe the interstitial lung disease-like pulmonary presentation of IVLBCL [18,19,20,21,22]. As shown by patients in this study, IVLBCL should be considered in the differential diagnosis of unexplained pulmonary presentations such as unexplained hypoxemia, interstitial lung disease or ground-glass opacity accompanied by systemic symptoms or signs of multi-organ involvement.…”
Section: Discussionsupporting
confidence: 77%
“…Only a few cases have been reported in Korea, and these have involved nonspecific radiological findings, including diffuse interstitial infiltrates, pleural effusion, signs of pulmonary hypertension, and tumor-like consolidation in the lungs. [4][5][6][7][8] No PET images of pulmonary IVL have been reported. Interestingly, two recent reports suggest that PET is useful for evaluating IVL.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with pulmonary IVL show nonspecific radiological findings, including diffuse interstitial infiltrates, pleural effusion, signs of pulmonary hypertension, and tumor-like consolidation in the lungs. [4][5][6][7][8] The usefulness of positron emission tomography (PET) in diagnosing IVL has not been established, but Odawara et al and 2. Lung window of a coronal reformatted CT scan shows extensive ground-glass opacity in both lungs except for some areas (arrows).…”
Section: Introductionmentioning
confidence: 99%
“…However, IVL with primary lung lesion is very rare and it is very difficult to diagnose before death. Ko et al [9]has reported 2 cases of IVL with primary pulmonary lesion. They also studied 204 cases of previously reported IVL and of these there were only 10 cases of IVL with primary pulmonary lesion [8, 10, 11, 12, 13, 14, 15].…”
Section: Discussionmentioning
confidence: 99%